2020
DOI: 10.1002/er.5626
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic and environmental investigation of an innovative poly‐generation plant driven by a solid oxide fuel cell for production of electricity, cooling, desalinated water, and hydrogen

Abstract: Fuel cell and renewable-based poly-generation plants (PGPs) are proven as advanced technologies for multiple generation purposes. To limit the greenhouse gas emissions, an innovative PGP generating electricity, cooling, desalinated water, and hydrogen is proposed in the current study. The system consists of a solid oxide fuel cell as a prime mover integrated with a gas turbine, a biomass combustion chamber, an organic Rankine cycle, an ejector refrigeration cycle, a desalination unit, and a proton exchange mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The input data in Table 1 have been utilized to simulate the CCHP system. The current study has also been simplified by considering the following assumptions [32][33][34][35] :…”
Section: Calculation Methodologymentioning
confidence: 99%
“…The input data in Table 1 have been utilized to simulate the CCHP system. The current study has also been simplified by considering the following assumptions [32][33][34][35] :…”
Section: Calculation Methodologymentioning
confidence: 99%
“…[51,52] Many researchers commonly utilize the following mathematical equations to evaluate the performance of SWH systems. [51,[53][54][55][56][57][58] These equations are supplemented with empirical data gathered from real-world experiments, which are then integrated into the equations for analysis and evaluation purposes. By employing these mathematical equations in conjunction with actual experimental data, researchers can obtain valuable insights into the performance and effectiveness of SWH systems.…”
Section: Mathematical Model For Swhmentioning
confidence: 99%
“…The equation for the rate of exergy destruction consists of two equations, [ 51 ] namely, Equation (28), which describes the loss resulting from the temperature difference between the sunlight and the plate, [ 66 ] and Equation (29), which quantifies the heat loss caused by the temperature difference between the absorber and the fluid passing through the collector. [ 66 ] Efalse.normald,ΔTnormalsnormalp=IT ηo Ac Ta(1TP1Ts)$$\left(\overset{.…”
Section: Mathematical Model For Swhmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, selecting one or more prime movers allows for the examination of polygeneration [81]. Studies have shown polygeneration structure optimization based on the chosen primary mover from a gas engine, PEMFC or SOFC.…”
Section: Evaluation Of Configuration Designmentioning
confidence: 99%